2015
DOI: 10.4321/s1578-84232015000200003
|View full text |Cite
|
Sign up to set email alerts
|

Dependencia al ejercicio físico e indicadores del estado de ánimo en deportistas universitarios

Abstract: Dependencia al ejercicio físico e indicadores del estado de ánimo en deportistas universitarios Exercise dependence and mood states indicators in university athletes Dependência ao exercício físico e indicadores do estado de ânimo em universitários esportistas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
3
3
0
7
Order By: Relevance
“…Regarding other variables, a multitude of studies and instruments have shown that the prevalence of sport addiction decreases with age, so it correlates inversely (Szabo [54]; Ruiz-Juan, Zarauz y Arbinaga [55]; Costa et al [56]). In addition, in our study, the number of sessions and their duration (Reche et al [36]; Reche and Gomez [57]) were found to be related to DPE.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Regarding other variables, a multitude of studies and instruments have shown that the prevalence of sport addiction decreases with age, so it correlates inversely (Szabo [54]; Ruiz-Juan, Zarauz y Arbinaga [55]; Costa et al [56]). In addition, in our study, the number of sessions and their duration (Reche et al [36]; Reche and Gomez [57]) were found to be related to DPE.…”
Section: Discussionsupporting
confidence: 56%
“…Sussman et al [35] observed that the prevalence of DPE in the general population of the USA to be between 3% and 5%. In a study on university students, Reche et al [36] found a DPE prevalence of 8% in athletes participating in individual sports. For Harris et al [37], it was between 16% and 36% depending on which degree they studied.…”
Section: Discussionmentioning
confidence: 99%
“…Tanto la resiliencia como la dependencia al ejercicio físico han sido constructos estudiados en función de distintas modalidades deportivas, individual y equipos (Chacón-Cuberos et al, 2016;Reche, Martínez-Rodríguez & Ortín, 2015), sin encontrar diferencias (Modolo, Mello, Giménez, Tufik & Antunes, 2009;Reche et al, 2015;Reche, De Francisco, Martínez-Rodríguez & Ros-Martínez, 2018), pero en ningún caso ha sido atendida la peculiaridad de los deportes de combate. Sin embargo, es más probable que la participación en ciertas actividades dé como resultado una mayor dependencia del ejercicio que en otras.…”
Section: Palabras Claveunclassified
“…Por otro lado, la prevalencia del riesgo de dependencia al ejercicio físico se ve representada por el 6.5 % de los participantes en el estudio, datos similares a otros estudios recientes, como el de Reche et al, (2019), con un 8.3 %. No se han encontrado diferencias por sexo en ninguna modalidad seleccionada, en la línea de investigaciones con deportistas de modalidad colectiva, individual y de combate (Reche et al, 2015;Reche et al, 2019;Reche-García, Montero & Martínez-Rodríguez, 2018); en deportistas de modalidad colectiva e individual (Cabrita, Rosado, De la Vega & Serpa, 2018); y de forma específica, en estudios con corredores y practicantes de ejercicio (Edmunds, Ntoumanis & Duda, 2006;Furst & Germone, 1993) y culturistas (Smith & Hale, 2004), corredores, nadadores, ciclistas y triatletas (Latorre et al, 2016); en corredores, ciclistas, duatletas y triatletas (Ortiz & Arbinaga, 2017); y en atletas de ironman (Magee, Buchanan & Barrie, 2016). Estos resultados difieren de lo encontrado por Weik y Hale (2009), quienes hallaron diferencias que señalaban que los hombres mantenían mayor riesgo de sintomatología relacionada con dependencia al ejercicio físico medida con el EDS-R, y diferencias que sugerían que eran las mujeres las que presentaban mayor riesgo siendo evaluadas con el EDQ y el DFT, que miden diferentes dimensiones de la dependencia al ejercicio físico.…”
Section: Resiliencia Deportes Deunclassified
“…Studies that analyze such factors are mostly framed within the scope of competitive sport. Nevertheless, other research within the field of the practice of leisure-time and health related PA have also been identified, where it has been noticed how physically active people present improved MS, with a lower presence of NMS (depression, stress or fatigue) and simultaneously a higher presence of the positive MS of "vigor" (Andrade et al, 2011;Berger and Motl, 2000;Chacón-Borrego et al, 2017;García et al,, 2015;Oiarbide, Martínez de Santos et al, 2014;Portela-Pino et al, 2017;Rey et al, 2000;Ruiz and Baena, 2011).…”
Section: Introductionmentioning
confidence: 99%